The study of thermo-physical properties of binary liquid mixtures of isoamyl alcohol with amines at 298.15–308.15 K. (3rd May 2020) - SavithaJyostna, T.; Satheesh, B.; Sreenu, D.; Ramesh, G.; Jayanthi Rani, E.
ABSTRACT: The values of density ( ρ ), viscosity ( η ) and speed of sound ( u ) were measured for binary mixtures of 3-methyl-1-butanol (isoamyl alcohol) with n -butylamine (NBA), sec-butylamine (SBA), tert-butylamine (TBA), n -hexylamine (NHA) and n -octyl amine (NOA) over the entire range of mole fractions and at three temperatures (298.15, 303.15 and 308.15 K). From these measurements, the values of excess molar volume( V E ), viscosity deviation ( ∆η ), deviation in isentropic compressibility ( ∆ks ), excess Gibbs free energy of activation of viscous flow ( G *E ) and Grungberg–Nissan interaction parameter ( d ′) have been calculated. The excess parameter deviations are fitted to Redlich–Kister-type polynomial equation using multi-parametric nonlinear regression analysis to estimate the binary coefficients and standard deviations. The results were discussed in terms of molecular interactions, dipole–dipole interactions and H-bond interactions between unlike molecules. Further, the effects of temperature and amine group in different amines were also studied for the binary mixtures.